Designing an ecofriendly and carbon-cum-energy efficient production system for the diverse agroecosystem of South Asia. (1st January 2021) - Kumar, Rakesh; Mishra, J.S.; Mondal, Surajit; Meena, Ram Swaroop; Sundaram, P.K.; Bhatt, B.P.; Pan, R.S.; Lal, Rattan; Saurabh, Kirti; Chandra, Naresh; Samal, S.K.; Hans, Hansraj; et al.
Abstract: There is an urgent need for identification of the eco-friendly/cleaner production system that is more productive and profitable; efficient user of energy, water, and carbon-based inputs, and also environmentally safer. The four years study was conducted from 2016 to 2019, where the dominant rice-wheat cropping system is practiced extensively after 'Green Revolution'. The objectives of the experiment were to evaluate: (1) energy budgeting, (2) carbon auditing, (3) production and economic efficiency of diverse cropping systems for upland rainfed as well as irrigated ecosystems of eastern India. Tillage and cropping system treatments were laid out according to a completely randomized block design and replicated thrice. Ten cropping sequences were comprised of: T1) a farmers' practice of transplanted rice-wheat-mungbean, T2) conventional till-direct seeded rice (CTDSR)-wheat-mungbean, T3) soybean-maize, T4) CTDSR-mustard-urdbean, T5) foxtail millet-lentil-fallow, T6) pearl millet-chickpea-fallow, T7) finger millet- toria -fallow, T8) sorghum (grain)-chickpea-fallow, T9) maize cob–pigeon pea, and T10) sorghum (fodder)-mustard-urdbean. Energy contributions of different inputs were 42–55, 12–21, 8–18, and 4–12% for fertilizers, diesel, labour, and electricity, respectively. The amount of indirect (fertilizer, chemicals, and machinery) and direct (diesel and electricity) non-renewable energy inputs were 40–60 and 18–26%, respectively. Indirect renewable energy input (seed and crop residues) was 1–7% as compared to 15–24% of direct-renewable energy (human labour and irrigation water). The maximum energy input was recorded for T1 (53511 MJ ha −1 ). The maximum biomass production (40.2 Mg ha −1 ) was recorded with T9, while the maximum benefit: cost ratio (3.64) was noted for T10 and T8. The highest specific energy (33.5 MJ kg −1 ) and energy productivity (0.92 kg MJ −1 ) were recorded in T8 treatment. Irrespective of cropping systems, retention of crop residues accounted for 28.6–58.5% of total carbon input. The carbon sustainability index was 5–7 times higher for the millet-based production system [T6 (9.32) and T8 (10.27)] compared to cereal-based systems [T1 (1.66) and T2 (1.21)]. Diversification of the rice-wheat system through climate-resilient millets-based production system reduced 84% energy consumption and 87% carbon footprint. The millet-based production system also helps in reducing the carbon input by 172% and improves the energy use efficiency by 61% compared to the cereal-based cropping system. Therefore, the study has an innovative idea to support the crop modelling, policymakers, government planners, researchers, and producers to achieve the sustainable development goals in Indo-Gangetic Plains and similar agro-climatic conditions of South Asia. Graphical abstract: Image 1 Highlights: Carbon-cum-energy efficient production system for the diverse agro-ecosystem of South Asia. The millet-based system reduced 84% energy use & 87% carbon-footprint than the rice-wheat system. Energy ratio in millet-based system increase 61% output and reduction 172% carbon -input. The millet-based had 56 & 58% more nutrient & non-renewable energy efficiency. The millet-based emerged as a viable alternative to the rice-wheat system.